Galois-type extensions and equivariant projectivity - Tomasz Brzezinski (Quantum Symmetry in Noncommutative Geometry, 2009)
. To be published by the (Tracts in Mathematics) in , PM Hajac, ed., Preprint 2009 arxiv:0901.0141 (with P.M.Hajac)